2016
DOI: 10.1002/prp2.244
|View full text |Cite
|
Sign up to set email alerts
|

Functional imaging of pharmacological action of SGLT2 inhibitor ipragliflozin via PET imaging using 11C‐MDG

Abstract: Sodium‐dependent glucose cotransporter 2 (SGLT2) is a pharmacological target of type 2 diabetes mellitus. The aim of this study was to noninvasively visualize the pharmacological action of a selective SGLT2 inhibitor ipragliflozin in the kidney using positron emission tomography (PET) imaging with 11C‐methyl‐d‐glucoside (11C‐MDG), an SGLT‐specific radio‐labeled substrate. PET imaging with 11C‐MDG in vehicle‐treated rats demonstrated that intravenously injected 11C‐MDG substantially accumulated in the renal cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Studies in knockout mice for SGLT2 or SGLT1 or SGLT2 plus SGLT1 have demonstrated that SGLT2 reabsorbs 80% to 90% glucose of the glomerular filtrate while SGLT1 reabsorbs the remaining 10-20% [71]. However, under acute [72] or chronic [73] SGLT2 inhibition or in SGLT2 knockout mice [73,74], a compensatory increase in SGLT1-mediated glucose transport explains 40-50% of its fractional reabsorption. This is observed early, even in the first hour of SGLT2 inhibition in murine models [72].…”
Section: Proximal Tubule Glucosementioning
confidence: 99%
See 1 more Smart Citation
“…Studies in knockout mice for SGLT2 or SGLT1 or SGLT2 plus SGLT1 have demonstrated that SGLT2 reabsorbs 80% to 90% glucose of the glomerular filtrate while SGLT1 reabsorbs the remaining 10-20% [71]. However, under acute [72] or chronic [73] SGLT2 inhibition or in SGLT2 knockout mice [73,74], a compensatory increase in SGLT1-mediated glucose transport explains 40-50% of its fractional reabsorption. This is observed early, even in the first hour of SGLT2 inhibition in murine models [72].…”
Section: Proximal Tubule Glucosementioning
confidence: 99%
“…However, under acute [72] or chronic [73] SGLT2 inhibition or in SGLT2 knockout mice [73,74], a compensatory increase in SGLT1-mediated glucose transport explains 40-50% of its fractional reabsorption. This is observed early, even in the first hour of SGLT2 inhibition in murine models [72]. SGLT1 vicariance justifies the maintenance of until 50% of the normal fractional glucose reabsorption during selective SGLT2 inhibition in humans [75][76][77].…”
Section: Proximal Tubule Glucosementioning
confidence: 99%
“…LA decreased the postprandial glucose level in the portal vein 15 min after glucose load ( Figure 2A ), so LA might inhibit glucose uptake via SGLT1 in the small intestine. α-MDG is a selective substrate of SGLTs ( Mitsuoka et al, 2016 ), and phlorizin is an antagonist of SGLT1 and SGLT2 ( Niederberger et al, 2020 ). CACO-2 cells from DSMZ were previously shown to efficiently express SGLT1, and α-MDG uptake in CACO-2 cells from DSMZ was at maximum efficiency 13 or more days after seeding ( Steffansen et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…a-Methyl-4-[ 18 F]-fluoro-4-deoxy-D-glucopyranoside is a high affinity SGLT1-substrate, a medium affinity SGLT2-substrate and a very low affinity GLUT-substrate, whereas 4-deoxy-4-[ 18 F]-fluoro-D-glucose is substrate for both GLUTs and SGLTs ( Sala-Rabanal et al, 2016 ). Mitsuoka et al used the SGLT1 and SGLT2-specific substrate [ 11 C]-methyl-d-glucoside to show an ipragliflozin-dose-related inhibition of [ 11 C]-methyl-d-glucoside reabsorption ( Mitsuoka et al, 2016 ). This shows that radiolabeled substrates can quantitate the glucose blocking potential of SGLT2i, but the individual contribution of SGLT1 and SGLT2 cannot be distinguished.…”
Section: Renal Oxygenation and Hypoxiamentioning
confidence: 99%